INVOLVING PARENTS IN THE SOCIAL ADAPTATION OF CHILDREN WITH DOWN SYNDROME - Nesterchuk, N. Ye.; Sydoruk, I. O. (Rehabilitation and Recreation, 2022)
Families raising children with Down syndrome experience difficulties in social inclusion and need comprehensive social support. In the article, we highlighted the stages of parents' reactions to the news that the child has a developmental disorder. Based on the analysis of domestic and foreign literature, the principles on which work with families should be built were determined. We formed three stages of parents' involvement in social adaptation. The first is initial, our main goal at this stage is the formation of parents' adequate ideas about the violation of the child's psychophysical development and the possibilities of his education and socialization. The second stage is organizational, a feature of this stage is the joint planning of various family events in accordance with the child's individual program and the development tasks indicated in it for a certain period. The final stage is communicative, this stage is crucial for the normalization of the psychological climate in the family. Today's scientific views are based on the conviction that parents are the first and main teachers of a child with Down syndrome, therefore social support for such families is a solution to a whole set of problems related to helping the child: treatment, education, social adaptation and integration into society. It is worth noting that for parents, working with children with Down syndrome is very difficult, since working with the child must be constant and intensive. It is important for the family to feel attention and support from specialists, interest in the child's development, readiness to help them, not to leave the parents alone with problems of interaction with the child.